Exogenous progesterone during in vitro fertilization improves developmental competence of partially cumulus-denuded bovine oocytes - Suqueli García, María Florencia; Gabbanelli, Nadia; Rios, Glenda Laura (Elsevier, 2023)
The progesterone (P4) secreted by cumulus cells has gained attention for its role as a possible physiological inducer of sperm acrosome exocytosis. In mammals, it is generally accepted that fertilization rates of oocytes without cumulus are markedly low. This study assessed the integrity of capacitated bovine sperm acrosome when exposed to increasing concentrations of P4, and evaluated whether exogenous P4 during in vitro fertilization (IVF) increases the developmental competence of partially cumulus-denuded oocytes in serum-free conditions. After a 4-h capacitation induction, sperm were incubated with increasing concentrations of P4 (0, 0.1, 10 and 100 μM) and evaluated for viability, caspase activation and acrosome status at three different times (4, 5, and 22 h), including the capacitation induction period. Progesterone induced sperm acrosomal exocytosis without compromising sperm viability or activating sperm caspases. Sperm undergoing acrosome reaction exhibited three differential Concanavalin A patterns, corresponding to early, intermediate and late acrosomal exocytosis. The percentage of these patterns significantly increased over time, regardless of P4 concentration, except for those spermatozoa with late acrosomal exocytosis, which only showed an increase at 22 h of incubation. After incubation for 1 h with 100 μM P4, spermatozoa showing intermediate acrosomal exocytosis significantly increased. At 22 h of incubation, the pattern corresponding to early acrosomal exocytosis evidenced a dose-dependent increase. However, prematurely high levels of acrosome reaction induced by 100 μM P4 led to inefficient IVF outcomes (P < 0.05). Therefore, IVF trials with partially cumulus-denuded oocytes were carried out with lower P4 concentrations (0, 0.1, 1, 5, 10 μM). Cleavage rate significantly increased at 1 μM P4, which translated to increased total embryo production after 7 days of in vitro culture (P < 0.05). Significantly higher percentages of expanded blastocysts were observed at both 1 μM and 10 μM P4 as compared to the other experimental conditions. In conclusion, the different patterns of acrosomal exocytosis identified over time by incubation of live sperm with a fluorescent lectin revealed the existence of sperm subpopulations heterogeneous in their physiological states. Moreover, exogenous P4 at 1 μM during IVF improved the developmental competence of partially cumulus-denuded oocytes in serum-free conditions.